Binding pattern of intermediate UDP-4-keto-xylose to human UDP-xylose synthase: Synthesis and STD NMR of model keto-saccharides. (2nd January 2017) - Puchner, Claudia; Eixelsberger, Thomas; Nidetzky, Bernd; Brecker, Lothar
Abstract: Human UDP-xylose synthase ( h UXS1) exclusively converts UDP-glucuronic acid to UDP-xylose via intermediate UDP-4-keto-xylose (UDP-Xyl-4O). Synthesis of model compounds like methyl-4-keto-xylose (Me-Xyl-4O) is reported to investigate the binding pattern thereof to h UXS1. Hence, selective oxidation of the desired hydroxyl function required employment of protecting group chemistry. Solution behavior of synthesized keto-saccharides was studied without enzyme via 1 H and 13 C NMR spectroscopy with respect to existent forms in deuterated potassium phosphate buffer. Keto-enol tautomerism was observed for all investigated keto-saccharides, while gem-diol hydrate forms were only observed for 4-keto-xylose derivatives. Saturation transfer difference (STD) NMR was used to study binding of synthesized keto-gylcosides to wild type h UXS1. Resulting epitope maps were correlated to earlier published molecular modeling studies of UDP-Xyl-4O. STD NMR results of Me-Xyl-4O are in good agreement with simulations of the intermediate UDP-Xyl-4O indicating a strong interaction of proton H3 with the enzyme, potentially caused by active site residue Ala 79 . In contrast, pyranoside binding pattern studies of methyl uronic acids showed some differences compared to previously published STD NMR results of UDP-glycosides. In general, obtained results can contribute to a better understanding in binding of UDP-glycosides to other UXS enzyme family members, which have high structural similarities in the active site. Graphical abstract: Highlights: Synthesis of model compounds to study binding of keto-xylose to h UXS1. Studying solution behavior of keto-saccharides in water by NMR spectroscopy. Monitoring binding pattern of keto-gylcosides to wild type h UXS1 using STD NMR. STD NMR results of Me-Xyl-4O are in agreement with earlier simulations.